Binary Particle Swarm Optimization for Scheduling MG Integrated Virtual Power Plant Toward Energy Saving - Hannan M.A.; Abdolrasol M.G.M.; Faisal M.; Ker P.J.; Begum R.A.; Hussain A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided software engineering; Controllers; Electromagnetic wave emission; Emission control; Energy conservation; Energy management; Energy utilization; Optimization; Particle swarm optimization (PSO); Power plants; Renewable energy resources; Binary particle swarm optimization; Carbon reduction; Micro grid; Reducing energy consumption; Scheduling controllers; Sustainable energy management; Virtual power plants; Virtual power plants (VPP); Scheduling